2020 IEEE Winter Conference on Applications of Computer Vision (WACV) 2020
DOI: 10.1109/wacv45572.2020.9093391
|View full text |Cite
|
Sign up to set email alerts
|

A "Network Pruning Network" Approach to Deep Model Compression

Abstract: We present a filter pruning approach for deep model compression, using a multitask network. Our approach is based on learning a a pruner network to prune a pre-trained target network. The pruner is essentially a multitask deep neural network with binary outputs that help identify the filters from each layer of the original network that do not have any significant contribution to the model and can therefore be pruned. The pruner network has the same architecture as the original network except that it has a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…. , m L [40]. m i represents the pruning mask of each layer of the network, which is usually represented by a binary matrix with the same dimension as w i .…”
Section: Neural Network Pruningmentioning
confidence: 99%
“…. , m L [40]. m i represents the pruning mask of each layer of the network, which is usually represented by a binary matrix with the same dimension as w i .…”
Section: Neural Network Pruningmentioning
confidence: 99%
“…As remote sensing imagery has become easier to obtain, many researchers have tried to use remote sensing data to drive intelligent applications based on DCNNs [3]. However, the over-parametrization problem of DCNNs hinders their application on resource-constrained remote sensing platforms [12][13][14]. Moreover, the work in the paper [22] has shown that the redundant parameters of DCNNs are necessary during network training.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, spaceborne or airborne platforms usually do not have high-speed Internet, and transmitting many remote sensing images to ground servers for processing will significantly consume valuable communication bandwidth. Therefore, the amount of parameters in DCNNs has become a bottleneck for object detection on resource-constrained platforms [11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%